2012
DOI: 10.1177/0270467612469074
|View full text |Cite
|
Sign up to set email alerts
|

Re-Mediating Research Ethics

Abstract: This article is a theoretical and empirical exploration of the meaning that accompanies contractual agreements, such as the End-User License Agreements (EULAs) that participants of online communities are required to sign as a condition of participation. As our study indicates, clicking “I agree” on the often lengthy conditions presented during the installation and updating process typically permits third parties (including researchers) to monitor the digitally-mediated actions of users. Through our small-scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Fragmented ownership structures present significant and yet to be fully realised consequences for the end consumers of DVGs and 795 this is particularly problematic given the multitude of evidence to suggest that EULAs and Terms of Service agreements are rarely read. In Chee, Taylor, and De Castell (2012) study of online gamers, only 3% reported that they read the entire contractual agreement and 62% read none of its content, a finding echoed in a range of contexts including social media (Debatin, Lovejoy Horn & Hughes, 2009;Gross & Acquisti, 800 2005), smartphone applications (Cotton & Bolan, 2012) and a broad array of thirdparty software (Bakos, Marotta-Wurgler, & Trossen, 2009). Even where contractual agreements are read their content may leave the consumer confused as to exactly what rights they hold, resulting in assumptions based on existing understandings of the relationship between possession and ownership (often drawing from experiences of material con-805 sumption).…”
Section: Discussionmentioning
confidence: 99%
“…Fragmented ownership structures present significant and yet to be fully realised consequences for the end consumers of DVGs and 795 this is particularly problematic given the multitude of evidence to suggest that EULAs and Terms of Service agreements are rarely read. In Chee, Taylor, and De Castell (2012) study of online gamers, only 3% reported that they read the entire contractual agreement and 62% read none of its content, a finding echoed in a range of contexts including social media (Debatin, Lovejoy Horn & Hughes, 2009;Gross & Acquisti, 800 2005), smartphone applications (Cotton & Bolan, 2012) and a broad array of thirdparty software (Bakos, Marotta-Wurgler, & Trossen, 2009). Even where contractual agreements are read their content may leave the consumer confused as to exactly what rights they hold, resulting in assumptions based on existing understandings of the relationship between possession and ownership (often drawing from experiences of material con-805 sumption).…”
Section: Discussionmentioning
confidence: 99%
“…Others point to unequal power dynamics between requesters and workers (Samuel, 2018), low compensation rates for completing HITs (Silberman et al, 2018), and the economically precarious circumstances that many crowd workers are in as reasons to question using crowdsourcing in the first place (Berg et al, 2018). And as in other areas of online-mediated research (e.g., Chee et al, 2012), questions of research ethics and the extent to which consent can be validated are not entirely resolved. Through a critical examination of crowdsourcing, this article offers a step toward improving conditions for requesters and workers, and addressing crowdsourcing's shortcomings as a research tool both methodologically and in terms of research ethics.…”
Section: Crowdsourcing As a Research Tool: A Brief Contextual Overviewmentioning
confidence: 99%
“…Increasing efforts on the part of games companies to automatically document the in-game activities of players has enabled quantitative researchers to amass and analyze large quantities of in-game data, often without players' explicit consent (Chee, Taylor, & de Castell, 2012). As we have shown, however, our study participants' involvement in EVE does not stop once they log off: a great portion of their involvement is conducted in spaces, and through practices, that are outside of New Eden and therefore, from the point of view of server-side logs, invisible.…”
Section: ''Multi-sited'' Playmentioning
confidence: 99%